RECEIVER OPERATING CHARACTERISTIC ANALYSIS OF SINGLE PREDICTORS OF POST-TRANSPLANT OUTCOMES IN KIDNEY TRANSPLANT RECIPIENTS (Global Conference on Medical and Health Sciences, 2026)
Accurate prediction of complications and survival after kidney transplantation remains a major clinical challenge due to the multifactorial nature of post-transplant outcomes. According to large registry data, early graft dysfunction, immunological risk, and donor-related factors account for up to 60–70% of early post-transplant adverse outcomes [1,3]. The present study aimed to evaluate the prognostic value of individual biochemical, immunological, and donor-related factors using receiver operating characteristic (ROC) analysis.
Keywords: Kidney transplantation; survival; ROC analysis; delayed graft function; KDPI; immunological risk; prognosis.